Analisis Kesalahan Pembentukan Kalimat Imperatif - Novliansyah, Ahtiandi; Saud, Syukur; Usman, Misnawaty (Universitas Negeri Makassar, 2024)
Abstract. This study aims to obtain data and information about the types of errors made in the formation of imperative sentences by students of SMA Negeri 8 Gowa. This type of research is a qualitative method which is interpretative-analytical. The data for this research is a corpus of data on the use of imperative clauses through questions asked by students. The data source for this research is the students of class XI IPS 4 SMA Negeri 8 Gowa, a total of 39 students. The results of the data analysis show that most of the errors made by the students in the imperative sentence are in the you-form with 103 errors or a percentage of 33.5%, in the you-form with 98 errors or a percentage of 33.8% and in the you-form with 89 errors or a percentage of 30.7%. In addition, the overall average score for errors in the use of imperative sentences made by students in class XI IPS 4 SMA Negeri 8 Gowa is 48.3%, which is in the high category.Keywords: Error analysis, imperative, sentence formation, German